EDUKASI HENTI JANTUNG PARU DAN PELATIHAN HANDS-ONLY CPR: BE A LIFESAVER - Sinulingga, Elysabeth; Saputra, Bima Adi; Meriana, Septa; Surbakti, Juwita Fransiska Br; Pailak, Heman (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Cardiopulmonary resuscitation (CPR) is an attempt to restore spontaneous circulation through high-quality uninterrupted chest compressions combined with respiratory support. A 2010 study by the American Heart Association (AHA) reported that adults who received compression-only CPR from a person survived better than those who did not receive any type of CPR. Other studies have also shown that the survival rates of adults who have cardiac arrest and are helped by someone who is not a health worker are similar, both Hands-Only CPR and conventional CPR (AHA, 2017). The purpose of this PkM is to increase knowledge, and skills in helping cardiac arrest and respiratory arrest in lay people before health workers come to help the methods used are starting with registration, pre-test, heart health education, cardiac arrest and respiratory arrest education, hands-only CPR education, and ending with a demonstration of hands-only CPR and post test. In the results of the pre-test and post-test education, the mean pre-test was 64 and the mean post-test was 83. The value added after the training was around 19 points for the seminar. Based on the results obtained, it can be concluded that this education increased knowledge and understanding of hands-only CPR.